2014
DOI: 10.1002/ldr.2334
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Study on Effects of Ground Managements on Soil Water and Available Nutrients in Jujube Orchards

Abstract: Soil erosion is a key factor affecting sustainable agriculture on Chinese Loess Plateau. A 2‐year study was conducted on jujube trees in a controlled study to compare effects of clean cultivation (CC) with jujube branch mulch (WJBM), strip white clover cover (SWC), strip shallow tillage (ST), jujube branch mulch under tree canopy + strip white clover cover (JBM + SWC) and jujube branch mulch under tree canopy + strip shallow tillage (JMB + ST). The study was on sloping soil (26·7%) in mesocosms (2·0 m × 0·8 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 57 publications
(70 reference statements)
0
29
0
Order By: Relevance
“…This directly increased the water consumption and then caused further decrease in deep soil water (Figure ). A serious decrease in deep soil water would lead to soil desiccation and ultimately to the formation of a dried soil layer in soil profile (Li, ; Wang et al ., ; Wang et al ., 2014). This can lead to negative impacts on ecosystem service by reducing available soil water for jujube surviving during drought.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This directly increased the water consumption and then caused further decrease in deep soil water (Figure ). A serious decrease in deep soil water would lead to soil desiccation and ultimately to the formation of a dried soil layer in soil profile (Li, ; Wang et al ., ; Wang et al ., 2014). This can lead to negative impacts on ecosystem service by reducing available soil water for jujube surviving during drought.…”
Section: Discussionmentioning
confidence: 99%
“…2013; König et al ., ). For example, fish‐scale pits, a semicircular rainwater retention basins building on the slopes in an alternating pattern that seems like fish scale, are used as a transitional measure for afforestation (Fu et al ., ; Li et al ., ;Wang et al ., 2014). Furthermore, researches on water‐saving pruning practice found that this kind of pruning practice could significantly decrease the transpiration and water consumption of jujube trees (Zhao et al ., ; Wei et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main factors that lead to non-sustainable soil erosion rates are: i) steep slopes; ii) disturbances of the soil profile during the planting of vines (Follain et al, 2012;Johnson et al, 1987); iii) topsoil compaction and decreased soil porosity under heavy machinery wheel traffic (Biarnès et al, 2012;Ferrero et al, 2005); iv) high runoff discharges; and v) tillage practices in the inter-rows. The key factor to understand soil erosion rates in vineyards is anthropogenic activity as agricultural management can reduce or increase soil losses and change soil properties as was found in different regions and under different crops (Costa et al, 2015;Nyssen et al, 2015;Parras-Alcántara et al, 2015Wang et al, 2016). Auerswald et al (2009) estimated an average soil loss value of 5.2 Mg ha À1 yr À1 from models using the RUSLE (Revised Universal Soil Loss Equation) for German vineyards.…”
Section: Introductionmentioning
confidence: 99%
“…Mulching involves maintaining a permanent or semi-permanent protective cover on the soil surface that can be composed of different materials such as vegetative residues, biological geotextiles, gravel and crushed stones (Cerdà, 2001;Gilley et al, 1986;Jordán et al, 2010;Mandal and Sharda, 2013;Smets et al, 2008;Xu et al, 2012;Zhao et al, 2013). The beneficial effects of mulching can be summarized as follows: i) increased water intake and storage (Cook et al, 2006;Mulumba and Lal, 2008), ii) protection of soil against raindrop impact, reducing erosion rates (Blavet et al, 2009;Jordán et al, 2010;Sadeghi et al, 2015a), iii) decreased sediment and nutrient concentrations in runoff (Cerdà, 1998;Gholami et al, 2013;Poesen and Lavee, 1991), iv) decreased runoff generation rates and surface flow velocity by increasing roughness (Cerdà, 2001;Jordán et al, 2010), v) improved infiltration capacity (Jordán et al, 2010;Wang et al, 2014), vi) increased activity of some species of earthworms and crop performance (Wooldridge and Harris, 1991), vii) enhanced soil physical conditions such as soil structure and organic content (De Silva and Cook, 2003;Jordán et al, 2010;Karami et al, 2012), viii) reduced topsoil temperature for more optimum germination and root development (Dahiya et al, 2007;Riddle et al, 1996) and decreased evaporation (Uson and Cook, 1995), and xix) enhanced interactions with nutrients (Campiglia et al, 2014;Movahedi Naeni and Cook, 2000). Among the different types of mulching, straw mulch is considered one of the most effective in achieving the above-mentioned benefits (Blavet et al, 2009;Dahiya et al, 2007).…”
Section: Introductionmentioning
confidence: 99%